Selective oxidation of methacrolein to methacrylic acid over H4PMo11VO40/C3N4-SBA-15. Issue 58 (23rd October 2019) - Zhou, Lilong; Zhang, Shanshan; Li, Zhengjie; Scott, Jason; Zhang, Zhikun; Liu, Runjing; Yun, Jimmy
Abstract : Molybdovanadylphosphoric acid (HPMV) was supported on a carbon nitride-modified SBA-15 (CN-SBA-15) molecular sieve to enhance its catalytic performance for oxidation of methacrolein (MAL) to methacrylic acid (MAA). Abstract : Molybdovanadylphosphoric acid (HPMV) was supported on a carbon nitride-modified SBA-15 (CN-SBA-15) molecular sieve to enhance its catalytic performance for oxidation of methacrolein (MAL) to methacrylic acid (MAA). HPMV/CN-SBA exhibited increased catalytic activity (20%) and five times greater MAA selectivity (98.9%) compared to bulk HPMV. HPMV supported on CN-SBA-15 exhibited much better catalytic performance as compared to that on other supports, such as KIT-6, HY zeolite, TiO2, Al2 O3, SiO2, CNTs, and NH3 -modified CNTs. The supported HPMV was well characterized by FT-IR, XRD, SEM, N2 physical desorption, TG-DTA, NH3 -TPD, CO2 -TPD, XPS, and solid-state NMR. The CN minimized the interaction between the silica support and HPMV. HPMV was successfully separated from SBA-15, which was restricted by CN to increase stability and prevent interaction between the catalysts and support that would lead to decomposition of the catalysts during calcination and reaction. HPMV reacted with amino groups on the CN, which improved MAA selectivity and enhanced the thermal stability of the supported heteropoly acid (HPA) catalysts. This work identifies a new approach to preparing highly efficient and stable supported HPA catalysts for oxidation reactions.